MEKANISME PEMBERHENTIAN KEPALA DAERAH BERDASARKAN PASAL 83 AYAT (1) UNDANG-UNDANG NOMOR 23 TAHUN 2014 TENTANG PEMERINTAHAN DAERAH - Siti Aminah (Wacana Hukum, 2018)
The mechanism for removing The Head of local goverment from the Office based on Article 83 Subsection (1) of Law Number 23 Year 2014 on local Government begins with the status of a head of local goverment being charged with criminal offense, followed by temporary removal from his/her office based on a register at a Court. It is also found that the officer in charge of removing a Head of local goverment is the President for an offending Governor and a Minister for an offending Regent or Mayor, without the need for a consultation with the local House of Representatives. Meanwhile, the legal consequences of a removal of a Head of local goverment  that the offender’s rights and responsibilities are assumed by Vice Head of local goverment, until a legally binding verdict on the matter has been issued by the Court. Whenever a Head of local goverment being indicted is not removed from his/her office, then the President or the Minister concerned may be charged of unlawful conduct that cause legal uncertainties within the bureaucracy of the regional government involved.